1987
DOI: 10.1098/rsta.1987.0082
|View full text |Cite
|
Sign up to set email alerts
|

The Oligocene and Miocene Outliers of West Cornwall and their Bearing on the Geomorphological Evolution of Oldland Britain

Abstract: OLIGOCENE AND MIOCENE OUTLIERS OF CORNWALL 213 held. There is indirect evidence that it formed subaerially over a long period during m id-Tertiary times; essentially, it appears to be an etchplain of tropical and subtropical origins, now largely stripped of its former saprolitic cover. It is demon strated that the grosser physiography of west Cornwall was established by the end of the Palaeogene at the latest and, also, that the area has probably never been inundated by Tertiary seas, except shallowly near to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 20 publications
(28 reference statements)
1
34
1
Order By: Relevance
“…6) is indeed a Mid-Pliocene wavecut platform, as was thought prior to the Walsh et al (1987) revision of the chronology (see online supporting information for details of their revision to the chronology and reasons for the subsequent reversion to the chronology assumed beforehand). Erosion of the palaeocliffline at its landward margin (Fig.…”
Section: Longer-timescale Landscape Evolutionmentioning
confidence: 99%
“…6) is indeed a Mid-Pliocene wavecut platform, as was thought prior to the Walsh et al (1987) revision of the chronology (see online supporting information for details of their revision to the chronology and reasons for the subsequent reversion to the chronology assumed beforehand). Erosion of the palaeocliffline at its landward margin (Fig.…”
Section: Longer-timescale Landscape Evolutionmentioning
confidence: 99%
“…A widespread planation surface of presumed middle Miocene age ('Reskajeage surface') is recognised across western Britain and beyond (Walsh et al, 1987(Walsh et al, , 1996Walsh, 1999). In north-east Scotland kaolin weathering took place in the middle Miocene under temperatures of 15 ± 5 °C (Hall et al, 2015).…”
Section: Neogenementioning
confidence: 99%
“…In fact, a series of benches has been identified along the coast and attributed to progressively lower transgressions in the Pliocene and Quaternary. This marine interpretation has been challenged by Walsh et al (1987Walsh et al ( , 1999 who showed the presence of deeply weathered rock and Oligocene (Chattian) and Miocene sediments within this regional surface. Similarly, Battiau-Queney (1984) reports that deeply weathered rock (up to 20 m) underlies this surface in Pembrokeshire in Wales.…”
Section: The Neogenementioning
confidence: 99%
“…Deep weathering profiles of a thickness up to 15 m have probably formed in less than 1 Ma. In North Wales and Derbyshire the Mio-Pliocene Brassington formation consists of pockets of what appear to be products of tropical weathering (Walsh et al 1972), while in Cornwall Walsh et al (1987Walsh et al ( , 1999 believe they have identified pockets of Miocene saprolite on an etchplain of tropical and subtropical origins. Similarly, Battiau-Queney (1984) claims to identify inselbergs, tropical planation surfaces and tropical weathering products in Wales.…”
Section: Possible Mechanisms Of Landscape Development In the Palaeogenementioning
confidence: 99%